South Africa’s legal framework to eradicate period poverty - Jonker, Vivienne (University of the Witwatersrand, Johannesburg, 2022)
A teenage girl attempting to complete high school in a low-income setting in South Africa is likely impeded by period poverty. Period poverty is the circumstance of women and girls1 being unable to manage their periods due to their socio-economic conditions. It compromises a plethora of human rights, such as the rights to education and equality. The South African state is legally obliged to ensure, at the very least, that these rights are not compromised. This paper equips the reader with an understanding of South Africa’s legal framework to address period poverty. It tells the story of the state’s measures to address period poverty; identifies their pertinent shortfalls and proposes amendments to the framework. Activists campaigning for the eradication of period poverty are encouraged to advocate for these amendments
A research report submitted in partial fulfilment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg,2022
Keywords: Low-income; South Africa; Poverty; Socio-economic conditions; Legal framework; UCTD; SDG-1: No poverty